Respiratory mechanics and gas exchanges in the early course of COVID-19 ARDS: a hypothesis-generating study - Diehl, J.-L. (Ann Intensive Care, 2020)
RATIONALE: COVID-19 ARDS could differ from typical forms of the syndrome. OBJECTIVE: Pulmonary microvascular injury and thrombosis are increasingly reported as constitutive features of COVID-19 respiratory failure. Our aim was to study pulmonary mechanics and gas exchanges in COVID-2019 ARDS patients studied early after initiating protective invasive mechanical ventilation, seeking after corresponding pathophysiological and biological characteristics. METHODS: Between March 22 and March 30, 2020 respiratory mechanics, gas exchanges, circulating endothelial cells (CEC) as markers of endothelial damage, and D-dimers were studied in 22 moderate-to-severe COVID-19 ARDS patients, 1 [1–4] day after intubation (median [IQR]). MEASUREMENTS AND MAIN RESULTS: Thirteen moderate and 9 severe COVID-19 ARDS patients were studied after initiation of high PEEP protective mechanical ventilation. We observed moderately decreased respiratory system compliance: 39.5 [33.1–44.7] mL/cmH(2)O and end-expiratory lung volume: 2100 [1721–2434] mL. Gas exchanges were characterized by hypercapnia 55 [44–62] mmHg, high physiological dead-space (V(D)/V(T)): 75 [69–85.5] % and ventilatory ratio (VR): 2.9 [2.2–3.4]. V(D)/V(T) and VR were significantly correlated: r(2) = 0.24, p = 0.014. No pulmonary embolism was suspected at the time of measurements. CECs and D-dimers were elevated as compared to normal values: 24 [12–46] cells per mL and 1483 [999–2217] ng/mL, respectively. CONCLUSIONS: We observed early in the course of COVID-19 ARDS high V(D)/V(T) in association with biological markers of endothelial damage and thrombosis. High V(D)/V(T) can be explained by high PEEP settings and added instrumental dead space, with a possible associated role of COVID-19-triggered pulmonary microvascular endothelial damage and microthrombotic process.